My Hero Academia. Vol. 23, Our brawl - Horikoshi, Kōhei, 1986-; Cook, Caleb D (VIZ Media, LLC, 2020)
"The final match of the battle training between Class A and Class B continues. Zapped by Shinso's mind control, Midoriya enters a fugue state where he meets on of the former users of One For All. What powerful Quirks have yet to be unlocked? Midoriya will surely need the full potential of One For All someday, but in the meantime, a new enemy--the Meta Liberation Army--begins to make its moves."--Page [4] of cover